Kesetaraan Gender dalam Perspektif Hukum Islam dan Pendekatan Gender dalam Pengkajian Islam - Sudirwan Sudirwan; Muh Rizki; Yudhi Asfar Fahruddin; Nurhijah Nurhijah; Muhammad Awaluddin; Deri Eka Putra (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Gender equality remains a significant discourse in contemporary Islamic studies, particularly in relation to how Islamic law (sharī’ah) is interpreted and applied within modern socio-cultural contexts. Traditional interpretations of Islamic texts have often been critiqued for reinforcing patriarchal readings, while contemporary scholarship increasingly emphasizes contextual and egalitarian approaches through gender-sensitive methodologies. This paper aims to examine gender equality from the perspective of Islamic law and to analyze the gender approach in Islamic studies as a methodological framework for reinterpreting classical Islamic texts. This research employs a qualitative method with a library research approach. Data were collected from primary sources such as classical fiqh literature and Qur’anic interpretations, as well as secondary sources including contemporary academic journals, books, and scholarly articles related to gender studies and Islamic jurisprudence. The data were analyzed using descriptive-analytical techniques to identify patterns of interpretation and conceptual developments regarding gender justice in Islam. The findings indicate that Islamic teachings fundamentally uphold principles of justice, equality, and human dignity, which can serve as a foundation for gender equity. However, interpretative diversity in classical jurisprudence has led to varying applications of gender roles. The gender approach in Islamic studies provides a critical and contextual framework that allows reinterpretation of texts in light of contemporary realities without departing from core Islamic principles. This approach contributes to a more inclusive understanding of Islamic law that supports gender justice within Muslim societies